Metode Preference Selection Index (PSI) Dalam Menentukan Calon Penerima Beasiswa Program Indonesia Pintar (PIP) - Sumarna Indra Permana (Jurnal ICT: Information Communication & Technology, 2022)
Information technology that is increasingly sophisticated and developing requires education to always adapt to technological developments, this is aimed at realizing an effective and efficient education. With the importance of education, the “Indonesia pintar” Program (PIP) is one of the government programs in the form of cash assistance given to children aged 6-21 years from poor families with the aim of easing the burden on parents and students to continue their education. However, in its implementation it is still not on target, so to overcome this, a decision support system is needed that can determine the priorities of prospective PIP scholarship recipients. In this study, a decision support system was designed using the PSI and Promethee methods with the criteria of parental occupation, parental income, student status and type of assistance program. This research was conducted at SMKN 1 Jamblang. The results of this study are that the SPK application using the PSI and Promethee methods can help the school in the process of submitting a pip scholarship candidate quickly and accurately.